DENDA PBB-P2 DAN KEPATUHAN WAJIB PAJAK: TINJAUAN HUKUM TATA NEGARA DAN RELEVANSINYA BAGI PENDAPATAN DAERAH - Muchammad Catur Rizky; Didit Darmawan (Fakultas Hukum Universitas Hang Tuah, 2026)
PBB-P2 is a type of tax that can be adjusted or changed based on rates set by the regional government based on the number of local residents (PAD) domiciled in an area. Land and Building Tax (PBB) is one of the most important components in the Indonesian tax system. This research applies normative juridical, which focuses on the analysis of positive legal norms and relevant data from Rural and Urban Land and Building Tax (PBB-P2), as well as its implications for regional tax and revenue needs. The essence of this research is that regional governments are constitutionally authorized to determine PBB-P2 fines as part of their fiscal autonomy based on Law No. 28 of 2009 concerning Regional Taxes and Regional Levies, However, due to the limited delegative authority of local governments in determining and implementing PBB-P2 taxes, there is the potential for deviation from the principle of legality. In addition, the application of fines does not fully reflect the principle of proportionality because the amount of the fine is not always proportional to the level of violation committed by the taxpayer. This can also be seen in the potential for unequal treatment of taxpayers due to differences in the social and economic conditions of the community. These conditions indicate that the application of PBB-P2 fines still tends to be oriented towards increasing regional revenue, so that the function of taxes as an instrument of justice, equality, and legal certainty in a democratic state based on the rule of law has not been fully realized.